Engineering of Floating Power Plant for River Flow Type Undershot 2 Waterwheels With 9 Fixed Blade and Butterfly Blade on Picohydro Scale - Suhartono, Suhartono; Fatmawati, Sri; Rudianto, Rahmat; Eko, Yanuar (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.102, 2017)
Central Kalimantan has the potential for very large water resources to discharge and relatively sufficient height when used as a source of new and renewable energy. Electrical energy needs of homes in remote areas such as rural areas in Central Kalimantan is necessary because of the uneven supply of electricity to all the villages, it is because it can not reach the electrical grid to a certain region of the city, although the area is a lot of source stream of flowing water can be used. From these things do research whose goal is to create a floating power plant that can work in a gentle stream picohydro scale and easy to maintenance and assembly, made with materials that are affordable and easy to obtain and can work well with the speed of water in Central Kalimantan. The results of field testing that has been done in a location that has the characteristics of the water velocity of 0.78 m / s up to 1.83 m / s can play a prototype design of a floating waterwheel well, the results of tests on 9 watt lamp load can turn on the lights and to produce power average lamp of 0.56 watts with an average water flow of 1.23 m3 / s with a waterwheel blade shape of butterflies as a more efficient form than the fixed blade remains in the research and can turn a generator up to 155.8 rpm and maximum power produced by the generator in the testing field is 115 Watts with an average voltage of 50 volts and an average current of 2.3 A